Idiopathic Hypereosinophilic Syndrome. A Clinical Case - E. A. Lopina; A. G. Dushina; R. A. Libis (SINAPS LLC, 2022)
Idiopathic hypereosinophilic syndrome is a rare phenomenon in medical practice. The main criterion for diagnosis is a persistent increase in the level of eosinophils above 1.5 * 109/ l in the blood serum and the absence of clinical and laboratory and instrumental data explaining the possible nature of this condition.A clinical case of idiopathic hypereosinophilic syndrome, which occurs under the guise of acute coronary syndrome, is presented. A detailed analysis of this case was carried out in order to highlight a possible variant of the course of this disease, as well as to increase alertness in the area of "large" eosinophilia.